Traditionally Catching and Processing of Laor in Moluccas Islands - Mahulette, Ferymon (Local Wisdom : Jurnal Ilmiah Kajian Kearifan Lokal, 2020)
Laor is a fishery product that found in Moluccas at March or April, a few days after the full moon. The swarming of laor in Moluccas is called timba laor. This event is one of the local wisdoms that must be conserved. The people have always consumed this worms for long time, but research of catching and processing techniques of laor has never been done. This research aimed to describe the techniques of catching and processing laor in Moluccas Province. This research was descriptive qualitative. Data was collected from direct observations and documentation from volunteers in several villages only in Moluccas Province, i.e. Latuhalat (Ambon), Booi (Saparua), Taruy (Geser), Elaar (Kei), and Emplawas (Tepa) villages. The catching and processing laor were very diverse in Moluccas. The people were usually catch of laor used a tanggo, both of triangular or oval shape. Laor that has been taken then processed into laor lawar and bakasang. Both of these food products were very popular in Moluccas community. This research was expected to conserve of timba laor culture to support the tourism in Moluccas province.DOI:Â https://doi.org/10.26905/lw.v12i2.4078